2010
DOI: 10.3325/cmj.2010.51.423
|View full text |Cite
|
Sign up to set email alerts
|

Pain to Hospital Times After Myocardial Infarction in Patients from Dalmatian Mainland and Islands, Southern Croatia

Abstract: Aim To analyze pre-hospital delay in patients with myocardial infarction from mainland and islands of Split-Dalmatian County, southern Croatia. MethodsThe study included all patients with myocardial infarction transported by ambulance to the University Hospital Split in 1999Split in , 2003Split in , and 2005. Pre-hospital delay was analyzed in the following intervals: pain-to-call, call-to-ambulance, ambulance-to-door, and door-to-coronary care unit interval. Patients were categorized according to the locati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Employed patients and patients with medical insurance were found to present to the hospital earlier. However some studies show that lack of medical insurance has no effect on hospital presentation time (27).…”
Section: Discussionmentioning
confidence: 99%
“…Employed patients and patients with medical insurance were found to present to the hospital earlier. However some studies show that lack of medical insurance has no effect on hospital presentation time (27).…”
Section: Discussionmentioning
confidence: 99%
“… 3 5 Between 1999 and 2005 the number of patients hospitalized due to MI in Central Dalmatia did not show increasing trends. 6 …”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that the pain-to-hospital times for MI patients from Central Dalmatia is too long compared to recommended standards. 6 Since 2005, percutaneous coronary intervention (PCI) is available as a hospital treatment in Central Dalmatia. 6 However, the effectiveness of this treatment depends on administration of thrombolysis shortly after the onset of symptoms, and the main cause of delay in patients reaching the hospital after MI is the time it takes the patient to decide that their symptoms require medical attention.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations